Venous thromboembolism risks and prophylaxis in King Fahad Hospital, Madinah, Saudi Arabia - Ayman Kharaba; Mohammad Al Aboud; Madinah Reham Kharabah; Khaled Alyami; Amal Al Beihany (Springer, 2019)
Objective: To evaluate the risk factors, physician's compliance, and implementation of the American College of Chest Physicians (ACCP) guidelines for venous thromboembolism (VTE) prophylaxis at our hospital. Methods: A retrospective cohort study was conducted in King Fahad Hospital, Madinah, Saudi Arabia, from July 2015 to September 2015. We used the ACCP 2012 guidelines to assess the VTE risk and to determine whether patients had received the recommended prophylaxis. All hospital inpatients aged 14 years or older were assessed for risk of VTE by reviewing the hospital chart. The primary endpoint was the rate of appropriate thromboprophylaxis. Results: A total of 414 patients were studied. Their mean age was 47.74 ± 20.4 years, and 208 (50.2%) were female. There were 292 (70.5%) patients at high risk and 73 (17.6%) at moderate risk. As per the ACCP criteria, 375 (90.5%) patients were at risk for VTE and qualified for prophylaxis. Although 227 (60.5%) received some form of prophylaxis, only 144 (38.4%) of them received ACCP-recommended VTE prophylaxis. Conclusion: In our hospital, most of the patients are at high risk for developing VTE. The VTE prophylaxis guideline is not properly implemented and is underutilized. Strategies should be developed and implemented to ensure patient safety.